That is not a question. Did you mean $270 to pesos? Or 3000 pesos to Us
Answer:
The equation of parabola is given by : ![(x-4) = \frac{-1}{3}(y+3)^{2}](https://tex.z-dn.net/?f=%28x-4%29%20%3D%20%5Cfrac%7B-1%7D%7B3%7D%28y%2B3%29%5E%7B2%7D)
Step-by-step explanation:
Given that vertex and focus of parabola are
Vertex: (4,-3)
Focus:(
,-3)
The general equation of parabola is given by.
, When x-componet of focus and Vertex is same
, When y-componet of focus and Vertex is same
where Vertex: (h,k)
and p is distance between vertex and focus
The distance between two points is given by :
L=![\sqrt{(X2-X1)^{2}+(Y2-Y1)^{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%28X2-X1%29%5E%7B2%7D%2B%28Y2-Y1%29%5E%7B2%7D%7D)
For value of p:
p=![\sqrt{(X2-X1)^{2}+(Y2-Y1)^{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%28X2-X1%29%5E%7B2%7D%2B%28Y2-Y1%29%5E%7B2%7D%7D)
p=![\sqrt{(4-\frac{47}{12})^{2}+((-3)-(-3))^{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%284-%5Cfrac%7B47%7D%7B12%7D%29%5E%7B2%7D%2B%28%28-3%29-%28-3%29%29%5E%7B2%7D%7D)
p=![\sqrt{(\frac{1}{12})^{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%28%5Cfrac%7B1%7D%7B12%7D%29%5E%7B2%7D%7D)
p=
and p=![\frac{-1}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B12%7D)
Since, Focus is left side of the vertex,
p=
is required value
Replacing value in general equation of parabola,
Vertex: (h,k)=(4,-3)
p=
![(x-h) = 4p(y-k)^{2}](https://tex.z-dn.net/?f=%28x-h%29%20%3D%204p%28y-k%29%5E%7B2%7D)
![(x-4) = 4(\frac{-1}{12})(y+3)^{2}](https://tex.z-dn.net/?f=%28x-4%29%20%3D%204%28%5Cfrac%7B-1%7D%7B12%7D%29%28y%2B3%29%5E%7B2%7D)
![(x-4) = \frac{-1}{3}(y+3)^{2}](https://tex.z-dn.net/?f=%28x-4%29%20%3D%20%5Cfrac%7B-1%7D%7B3%7D%28y%2B3%29%5E%7B2%7D)
The volume of a rectangular prism is width×length×width. With the given volume of 24 you could find 2 ways with different sets of numbers that multiply into 24.
Oliver's= 6, 2, 2
Layla, 3, 2, 4
<h2>
Answer:</h2>
We will use substitution to solve this system for x.
![x - 2y = 27\\y = 5x\\\\x - 2(5x) = 27\\\\x - 10x = 27\\\\-9x = 27\\\\x = -3](https://tex.z-dn.net/?f=x%20-%202y%20%3D%2027%5C%5Cy%20%3D%205x%5C%5C%5C%5Cx%20-%202%285x%29%20%3D%2027%5C%5C%5C%5Cx%20-%2010x%20%3D%2027%5C%5C%5C%5C-9x%20%3D%2027%5C%5C%5C%5Cx%20%3D%20-3)
Now that we know what x is, we can determine y by pluging in -3 for x in one of the original equations. I will use the first one.
![-3 - 2y = 27\\\\-2y = 30\\\\y = -15\\](https://tex.z-dn.net/?f=-3%20-%202y%20%3D%2027%5C%5C%5C%5C-2y%20%3D%2030%5C%5C%5C%5Cy%20%3D%20-15%5C%5C)
We now have our solution.
D. ![(-3, -15)](https://tex.z-dn.net/?f=%28-3%2C%20-15%29)
We can check our answer by pluging the solution into one of the original equations to see if both sides equal each other. I will use the first equation.
![-3 - 2(-15) = 27\\\\-3 + 30 = 27\\\\27 = 27](https://tex.z-dn.net/?f=-3%20-%202%28-15%29%20%3D%2027%5C%5C%5C%5C-3%20%2B%2030%20%3D%2027%5C%5C%5C%5C27%20%3D%2027)
Since the equation checks out, our solution is correct.